Building Bridges in Cardio-Oncology: The Role of Clinics in Multidisciplinary Care and Patient Outcomes - Laksono, Sidhi (http://dharmais.co.id/, 2025)
Cardio-oncology is a specialized field within cardiology that focuses on the relationship between cancer, its therapies, and cardiovascular health. This multidisciplinary domain, involving cardiology, hematology, and oncology, addresses the significant cardiovascular risks associated with cancer treatments, particularly chemotherapy, which can lead to conditions such as heart failure, coronary artery disease, myocarditis, and pericardial effusion. Developing robust clinical pathways is essential to mitigate these risks and ensure timely diagnosis and management of therapy-induced cardiac dysfunction. Cardio-oncology clinics play a pivotal role in integrating multidisciplinary expertise, providing consultation and heart evaluation services, and fostering research to improve patient outcomes. Strengthening collaboration across disciplines and raising awareness among patients are critical goals in advancing the effectiveness of cardio-oncology clinics.